2009
DOI: 10.1007/s11095-009-9978-z
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Iontophoresis of Amino Acids: Identification and Separation of Stratum Corneum and Subdermal Sources In Vitro

Abstract: A relatively short extraction period (approximately 1 h) by reverse iontophoresis can be used to evaluate the content of AAs in the SC. Once this 'reservoir' has been depleted, reverse iontophoresis can then monitor the subdermal concentrations of the AAs. The latter appears most useful for compounds which are present at lower levels in the SC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…The skin may also accumulate the analyte of interest such that the initial extraction sample contains mostly information about this local "reservoir" (this is the case for glucose [36], lithium [28], urea [49][50][51], lactate [30], and many amino acids [52][53][54]). A "warm-up" period is necessary to empty this reservoir before the iontophoretic fluxes are reflective of systemic levels.…”
Section: Overviewmentioning
confidence: 99%
“…The skin may also accumulate the analyte of interest such that the initial extraction sample contains mostly information about this local "reservoir" (this is the case for glucose [36], lithium [28], urea [49][50][51], lactate [30], and many amino acids [52][53][54]). A "warm-up" period is necessary to empty this reservoir before the iontophoretic fluxes are reflective of systemic levels.…”
Section: Overviewmentioning
confidence: 99%
“…The aims included solving the calibration issue in glucose sampling but also exploring other therapeutic monitoring and clinical chemistry applications. The significant amount work performed with glucose, mannitol, valproate, phenytoin, lithium, caffeine, theophylline, urea, iohexol, phenylalanine and other amino acids [65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82] provided an extensive framework to which we owe clear mechanisms of extraction, feasibility and range of applications - pharmacokinetic profiling, non-invasive therapeutic monitoring and skin health - for the technique. Key issues have been identified such as the impact of plasma binding, of kinetics (i.e.…”
Section: Iontophoresismentioning
confidence: 99%
“…As key examples, Sieg et al [66,67,68,69,70,71] and Nixon et al [72] explored the use of an internal standard method to solve the calibration issue, and Leboulanger et al [73,74,75] demonstrated the feasibility of non-invasive therapeutic monitoring of lithium in bipolar patients. An interesting development was the exploitation of the skin reservoir [76,77,78,79,80,81,82]. Reverse iontophoresis had been initially proposed as a non-invasive method to obtain systemic levels of drugs and markers, therefore the local ‘reservoirs' found for glucose, lithium, urea, lactate and many amino acids [69,70,71,72,73,77,79,81,82] were considered a drawback.…”
Section: Iontophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Th e results indicated that the reverse iontophoresis have the potential of extracting diff erent amino acids and can provide a reliable correlation [53]. Rapid extraction of amino acids by reverse iontophoresis after tape stripping was demonstrated [54]. Application of reverse iontophoresis was explored by assessing the feasibility of extracting phenylalanine an amino acid used to diagnose Phenylketonuria (metabolic disease in infants).…”
Section: Studies On Therapeutic Drug Monitoringmentioning
confidence: 99%